Lo stato di diritto non è a geometria variabile - Marsili, M. (Nonmollare, 2025)
English abstract This article critiques the selective application of international law, arguing that geopolitical interests undermine the credibility of global justice institutions like the International Criminal Court (ICC). Analyzing cases involving Vladimir Putin, Benjamin Netanyahu, Mohammed bin Salman, and U.S. military interventions, the author demonstrates pervasive double standards in prosecuting war crimes and territorial annexations. Powerful states (e.g., the U.S., Russia, Israel) evade accountability despite violations, while weaker actors face scrutiny. Marsili warns that such inconsistency erodes trust in international law, fuels revisionism, and perpetuates injustice. He calls for reaffirming universal legal principles, invoking Martin Luther King’s axiom that "injustice anywhere threatens justice everywhere." Failure risks a chaotic world where law becomes a tool of power, disproportionately harming the vulnerable. Italian abstract L’articolo denuncia l’applicazione selettiva del diritto internazionale, sostenendo che gli interessi geopolitici minano la credibilità di istituzioni come la Corte penale internazionale (Cpi). Attraverso casi che coinvolgono Vladimir Putin, Benjamin Netanyahu, Mohammed bin Salman e interventi militari statunitensi, l’autore evidenzia un doppiopesismo nella persecuzione di crimini di guerra e annessioni territoriali: le potenze (Usa, Russia, Israele) evitano sanzioni nonostante le violazioni, mentre gli attori deboli subiscono azioni giudiziarie. Marsili avverte che questa incoerenza danneggia la fiducia nell’ordine internazionale, alimenta revisionismi e consolida l’impunità. Invocando il principio di Martin Luther King ("un’ingiustizia ovunque minaccia la giustizia ovunque"), esorta a riaffermare la natura universale e imparziale dello stato di diritto. L’alternativa è un caos normativo in cui i più deboli soccombono.